2020
DOI: 10.1016/j.drugalcdep.2020.108166
|View full text |Cite
|
Sign up to set email alerts
|

Explication of CB1 receptor contributions to the hypothermic effects of Δ9-tetrahydrocannabinol (THC) when delivered by vapor inhalation or parenteral injection in rats

Abstract: The use of ∆ 9 -tetrahydrocannabinol (THC) by inhalation using e-cigarette technology grows increasingly popular for medical and recreational purposes. This has led to development of e-cigarette based techniques to study the delivery of THC by inhalation in laboratory rodents. Inhaled THC reliably produces hypothermic and antinociceptive effects in rats, similar to effects of parenteral injection of THC.This study was conducted to determine the extent to which the hypothermic response depends on interactions w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
(109 reference statements)
4
8
1
Order By: Relevance
“…Rats had ad libitum access to food and water in their home cages and all experiments were performed in the rats' scotophase. Sample sizes were estimated based on results of prior studies investigating the effects of acute drug exposure on the telemetry endpoints (Aarde et al, 2017;Javadi-Paydar et al, 2018b;Nguyen et al, 2017;Nguyen et al, 2020a); group size was initially N=8 but two animals were initially lost due to surgical complications. All procedures were conducted under protocols approved by the Institutional Care and Use Committee of the University of California, San Diego.…”
Section: Subjectsmentioning
confidence: 99%
“…Rats had ad libitum access to food and water in their home cages and all experiments were performed in the rats' scotophase. Sample sizes were estimated based on results of prior studies investigating the effects of acute drug exposure on the telemetry endpoints (Aarde et al, 2017;Javadi-Paydar et al, 2018b;Nguyen et al, 2017;Nguyen et al, 2020a); group size was initially N=8 but two animals were initially lost due to surgical complications. All procedures were conducted under protocols approved by the Institutional Care and Use Committee of the University of California, San Diego.…”
Section: Subjectsmentioning
confidence: 99%
“…It required 60 minutes of exposure to THC to produce any significant effect (Figure 5B), which was very small in magnitude. Although THC has limited anti-nociceptive impact in rodents relative to an opioid (Nguyen et al, 2019) and has a limited dose-effect range due to this low ceiling, it is typically more robust in rodents than what was observed here.…”
Section: Discussionmentioning
confidence: 52%
“…It is thus of interest to develop assays to determine if lobsters exhibit thermal nociceptive behavioral responses and then to determine if those responses can be altered by THC exposure. The hot-water tail withdrawal assay in rats involves a reflexive tail movement when it is inserted in hot water (~48-52°C) and has been shown to be altered in rats after vapor inhalation of THC (Javadi-Paydar et al, 2018; Nguyen et al, 2016; Nguyen et al, 2020). Thus, one goal was to determine if a warm water immersion test of nociception is functional in the lobster and if so, if THC exposure decreased thermal nociception as it does in rodents (Tseng and Craft, 2001; Wiley et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This is a novel observation since we did not include this in our prior study (Gutierrez et al, 2020a) which was the first to show efficacy of EDDS vapor delivery of heroin. While the effect of naloxone is perhaps expected, we’ve reported an unanticipated lack of effect of CB 1 antagonist/inverse agonist pre-treatment on THC vapor-induced hypothermia (Nguyen et al, 2020), so it was important to confirm opioid antagonist efficacy in this model. The failure to achieve a statistically reliable additive anti-nociceptive effect of heroin inhalation in the female group is likely due to a slightly more robust response to the heroin inhalation condition, compared with the males.…”
Section: Discussionmentioning
confidence: 98%
“…An opioid receptor antagonist study was included because we had not included this evidence in a prior study reporting heroin vapor effects on similar endpoints (Gutierrez et al, 2020a) and we’ve reported an unusual lack of effect of cannabinoid receptor 1 (CB 1 ) antagonist/inverse agonist pre-treatment on THC vapor-induced hypothermia (Nguyen et al, 2020). This latter was observed despite efficacy against the anti-nociceptive effects of inhaled THC and the thermoregulatory effects in injected THC thus it was of interest to determine if a nonselective opioid receptor antagonist was effective against effects of inhaled heroin on temperature, activity and anti-nociceptive responses.…”
Section: Methodsmentioning
confidence: 99%